"We Faced Every Change Together". Couple's Intimacy and Sexuality Experiences from the Perspectives of Transgender and Non-Binary Individuals' Partners. Issue 1 (2nd January 2022) - Siboni, Laura; Rucco, Daniele; Prunas, Antonio; Anzani, Annalisa
Abstract: In recent years, there has been a growing interest in the study of transgender and non-binary (TGNB) individuals' romantic and sexual relationships. The present study explored, from TGNB people's partners' perspective, how the couple experiences sexuality and intimacy, the effects from gender dysphoria in these relational domains, and how dysphoria is managed. For this purpose, 99 partners of TGNB individuals were recruited for an online study. Participants were asked to answer the following open-ended questions: "In the intimacy and sexuality with your partner, are there any parts of your or your partner's body that are/were off-limits?" "How did you manage this before, during, and after transition?" The data were analyzed through thematic analysis, and four overarching themes emerged: 1) Positive Aspects of the Relationship; (2) Challenges; (3) Strategies to Manage Dysphoria; and (4) Expected Improvement through Access to Medical Affirmation. The results suggest that gender dysphoria is one of the main challenges in experiencing intimacy and sexuality, but TGNB individuals and their partners can rely on several relational and practical resources to navigate it and enjoy positive experiences with intimacy and sexuality. The findings provide valuable information about how TGNB individuals and their partners build healthy and fulfilling relationships, and they can help clinicians better understand both members' perspectives in these romantic couples in the context of couples' therapy and sexual counseling.